2021
DOI: 10.1002/ppul.25264
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in children with asthma

Abstract: Asthma and sleep disorders are both common in childhood, and often co‐exist in the same child. Moreover, studies have shown that in many children the rate of one is influenced by the other. Sleep disorders can be classified into six different groups—insomnia, hypersomnia, parasomnia, movement disorders, circadian disorders, and sleep‐related breathing disorders. Children with asthma often present with complaints of insomnia with poor sleep quality, difficulty falling asleep and sleep disruptions. These complai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…“Sleep disorders” is an umbrella term that includes several aspects of sleep including sleep quality/satisfaction/duration, daytime sleepiness, circadian rhythm and sleep disordered breathing (SDB). The prevalence of sleep disorders depends on which aspect is studied, but on the whole, sleep disorders are generally described as common in childhood 105,106 . Exploring the relationship between asthma and sleep disorders has been of interest for decades, in particular the role of asthma severity and asthma control as sleep can be disturbed by nocturnal asthma symptoms 106 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…“Sleep disorders” is an umbrella term that includes several aspects of sleep including sleep quality/satisfaction/duration, daytime sleepiness, circadian rhythm and sleep disordered breathing (SDB). The prevalence of sleep disorders depends on which aspect is studied, but on the whole, sleep disorders are generally described as common in childhood 105,106 . Exploring the relationship between asthma and sleep disorders has been of interest for decades, in particular the role of asthma severity and asthma control as sleep can be disturbed by nocturnal asthma symptoms 106 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have found an inverse relationship between PSQ score and Asthma Control Test (ACT) score ( p < .001), 121–123 suggesting an association between SDB and poor asthma control. It has been proposed that the bidirectional association between asthma and SBD is due to inflammation in the “united airway,” for example, those with uncontrolled asthma have been found to have higher levels of tonsil TNF‐α compared to children with well‐controlled asthma 105,124 …”
Section: Resultsmentioning
confidence: 99%
“…Among all sleep disorders it represents the most frequent in the asthmatic adolescent [62,63] and, despite these findings, is underestimated, poorly characterized, little faced. Insomnia can be secondary to asthma and its therapies [64], be present independently [65], or both with the creation of a vicious circle that is self-sustaining with serious consequences on health and more (Figure 1).…”
Section: Adolescents Asthma and Sleep Disordersmentioning
confidence: 99%
“…Among all sleep disorders it represents the most frequent in the asthmatic adolescent [62,63] and, despite these findings, is underestimated, poorly characterized, little faced. Insomnia can be secondary to asthma and its therapies [64], be present independently [65], or both with the creation of a vicious circle that is self-sustaining with serious consequences on health and more (Figure 1). Poorly controlled asthma, weight gain, depression, mental capacity reduction, tendency to illicit drug use, poor scholastic performance, and problems in social and familiar spheres, are just a few of the many consequences [66].…”
Section: Adolescents Asthma and Sleep Disordersmentioning
confidence: 99%
See 1 more Smart Citation